Angiotensin receptor blockers are equally effective in women and men; a systematic review and meta-analysis. (3rd October 2022) - Laven, S; Mohseni-Alsalhi, Z; Meijs, D; Vaes, E; Wilmes, N; Van Luik, E; Vesseur, M; De Haas, S; Spaanderman, M; Ghossein-Doha, C
Abstract: Background: Hypertension is the leading risk factor for cardiovascular disease (CVD) and is the most substantial and neglected health burden in women. While treatment of high blood pressure is essential in the global prevention strategies of CVD it is assumed that effectiveness of pharmacological treatment may be hampered by sex differences. However, it is still not known whether sex differences exist in the effect of the antihypertensive medications. Purpose: To evaluate sex-stratified effects for angiotensin receptor blockers (ARBs) on blood pressure (BP) and cardiac function in female compared to male hypertensive participants. Methods: A series of systematic reviews and meta-analysis was performed. PubMed and EMBASE were systematically searched for studies evaluating the effects of the five major groups of antihypertensive medication from 1945 to May 2020. Randomized control trials and observational studies in humans (≥18 years) were included investigating beta-blockers (BB), angiotensin converting enzyme inhibitors (ACE-I), angiotensin receptor blockers (ARB), calcium channel blockers (CCB), and diuretics. In this study data on ARB's was analyzed. Studies had to present both baseline and follow-up measurements of at least one of the outcome variables of interest and present their data in a sex-stratified manner. Data on BPand cardiac function where retrieved from studies. Risk of bias was assessed using the Cochrane risk of bias tool. Results: The search strategy resulted in 73, 867 hits. After first screening based on title and abstract, 15, 130 articles where suitable for full test screening. After excluding all studies that matched the exclusion criteria, 205 studies with 15, 570 participants where eligible for analysis for the five antihypertensive drugs. Studies investigating ARB's (n=17) where used in this review. Seven trials (41%) had a low risk of bias. ARB decreased BP significantly and comparably in both women and men. Systolic BP −18.2 mmHg (95% CI, −24.8 to −11.5) vs −20.1 mmHg (95% CI, −26.7 to −13.6) and diastolic BP −11.6 mmHg (95% CI, −14.7 to −8.4) vs −12.3 mmHg (95% CI, −16.4 to −8.1). LVEF did not change significantly in either group. LV mass was only reported in males and did not change significantly −11.8 g (95% CI, −25.6 to 1.9). Conclusion: Our meta-analysis shows that based on the current studies, no sex differences exists in the effect of ARB on blood pressure or cardiac function. Funding Acknowledgement: Type of funding sources: None.